KINKAKU-JI TEMPLE (International journal of artificial intelligence, 2026)
this article is devoted to an academic study of Japan’s Kinkaku-ji Temple. The historical origin of the temple, its construction and author, as well as its architectural and cultural significance are analyzed. The views of scholars are examined and compared with the new approach proposed in the article. The study presents Kinkaku-ji Temple as a scholarly, historical, and cultural object.